Theology After Derrida. (22nd April 2013) - Horner, Robyn
Abstract It has recently been argued that Derrida's work is thoroughly atheistic, which seems to put any dialogue between Derrida and theology out of play. However, such arguments forget that to forbid the impossible outright is as much to be a slave to metaphysics as to presume that one could attain to it in language. Here I revisit the relationship between deconstruction and negative theology, and reconsider utilising Derrida to think God as the impossible. Arguing that thinking God in the absolute future still cannot sustain theology, I suggest how Derrida's work might nevertheless open onto the possibility of revelation.